Influence of oxygen and boron distribution on superconducting characteristics of nanostructural Mg-B-O ceramics - Prikhna, T. A.; Gawalek, W.; Kozyrev, A.; Eisterer, M.; Weber, H. W.; Moshchil, V.; Karpets, M.; Basyuk, T.; Sverdun, V.; Kovylaev, V.; Shaternik, A.; Chaud, X.; et al. (Видавництво Львівської політехніки, 2012)
Nanostructural superconducting MgB2-based materials contain a great quantity of O, which gives grounds to assign them to Mg-B-O compounds. The quantity of O in these materials is not an obstacle for attaining high critical current density (jc=106 A/cm2 in 1 T at 20 K), upper critical magnetic fields (Bc2(0 K)= 42 Т, Bc2(22 K)= 15 Т) and the fields of irreversibility (Br(0 K)= 32.5 Т, Br(18.5 K)= 15 Т). Our recent studies have shown that by changing manufacturing conditions (temperature, pressure, adding Ti, SiC) is possible to affect oxygen and boron distribution in the structure of Mg-B-O ceramic materials and purposefully change the type of pinning, superconducting properties, thus varying their behavior in magnetic fields.
Keywords: MgB2-based superconductors; critical current density; upper critical field; pinning; connectivity